Strategy, Sun Tzu and the Battle of Marathon. Issue 1 (2nd January 2021) - Ploumis, Michail
ABSTRACT: On the occasion of the anniversary of 2.500 years since the culmination of the Greco-Persian Wars (499-449 BC), the article attemps to showcase the concurrence of the strategy implemented at the Battle of Marathon (490 BC) by the Greek General Miltiades and the maxims of war established by the great Chinese General and philosopher Sun Tzu (544-496 BC). The aforemontioned battle is selected as a paradigm of the military history of the western world, demonstrating the implementation of the axioms of the great theoritician and practitioner of war. It attempts on overview of bibliography on strategy and more specifically on the precepts of Sun Tzu. It gives a brief account of the planning and conduct of the battle and makes an analysis of their concurrence with the teaching and principles of the Chinese philosopher.